CORRELATIONS BETWEEN THE PHYSICAL EDUCATION TEACHER’S TEACHING STYLE AND THE PERCEPTIBLE MOTIVATIONAL LEVEL OF THE LEARNING ENVIRONMENT - Lappints, Regős; H. Ekler, Judit (Stadium - Hungarian Journal of Sport Sciences, 2024)
The goals of physical education teaching today go beyond achieving psychomotor activity in the classroom. The most crucial objective of the subject is to develop the child’s need for physical activity both in the classroom and outside the school environment. To achieve this, physical activity motivation must become intrinsic, which physical education teachers can help achieve by using teaching styles and methods that promote autonomy and ensure that each pupil has the opportunity to develop. In our research, based on the answers to the questionnaire validated by the Hungarian Student Sports Federation, we selected physical education teachers with a predominantly student-centered or predominantly teacher-centered teaching style. We asked a sample of physical education teachers about their attitudes and sporting habits toward physical education lessons using a PMCSQ-2 questionnaire. The results confirmed the motivational effects of student-centered teaching styles.